Digitalization of Promotion Through Liaison Officer Assistance for Tahu Gejrot and Es Teler Creamy Buk Tuty MSMEs at Polbeng Business Expo Chapter II - Najwa Muthia Ramadhani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Polbeng Business Expo Chapter II, held at State Polytechnic of Bengkalis on 20–22 May 2025, provided a promotional platform for local Micro, Small, and Medium Enterprises (MSMEs). This study aims to describe the digitalization of promotion through Liaison Officer (LO) assistance for Tahu Gejrot and Es Teler Creamy Buk Tuty, encompassing preparation, implementation, and project completion. A descriptive qualitative approach was applied through direct observation, interviews with the business owners, and activity documentation. The assistance process included compiling business profiles, producing two profile videos, creating thirty promotional videos and thirty digital product catalogs, and conducting one month of digital marketing before the expo. Promotional content was distributed through Instagram, Facebook, TikTok, and WhatsApp Status, supported by two paid influencer collaborations using local Bengkalis accounts. During the three-day exhibition, Tahu Gejrot sold 44 portions and generated IDR 440,000, while Es Teler Creamy Buk Tuty sold 97 portions and generated IDR 970,000. The findings show that LO assistance functioned not only as an operational communication bridge between organizers and tenants but also as an integrated promotional facilitator combining content production, multi-platform dissemination, paid promotion, and sales documentation. This structured assistance increased product visibility, strengthened MSME promotional readiness, and supported measurable sales performance during a short-term business exhibition. The study highlights the importance of practical digital mentoring for local MSMEs with limited promotional resources.